2011
DOI: 10.1039/c1an15506g
|View full text |Cite
|
Sign up to set email alerts
|

Detection and analysis of airborne particles of biological origin: present and future

Abstract: Detection and identification of bioaerosols in the environment presents a unique analytical challenge. The complexity and variation of the analyte, coupled with the disparity of the end users required information has led to the establishment of a huge number of approaches for detection. In general these approaches may be divided into two elements; sampling, describing the physical process used to capture the bioaerosols and analysis, the method by which the bioaerosols are counted and identified. There are a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 124 publications
0
26
0
Order By: Relevance
“…Chemical and optical properties of PBAP samples or their tracers can be monitored in real time by chromatography, mass spectrometry, fluorescence spectrophotometry, lidar, and flow cytometry. Short overviews of PBAP analysis techniques have been given by Caruana (2011) and Després et al (2012). This paper focuses on the mesoscale simulation of atmospheric concentrations of fungal spores.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical and optical properties of PBAP samples or their tracers can be monitored in real time by chromatography, mass spectrometry, fluorescence spectrophotometry, lidar, and flow cytometry. Short overviews of PBAP analysis techniques have been given by Caruana (2011) and Després et al (2012). This paper focuses on the mesoscale simulation of atmospheric concentrations of fungal spores.…”
Section: Introductionmentioning
confidence: 99%
“…Caruana (2011) observed that relatively few studies have been published on the applicability of electrostatic precipitation to collect bioaerosols. However, interest in electrostatic methods is growing and studies recently showed that it is a suitable method to collect microorganisms (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms have also been shown to be transported over long distances with desert dust from Asia and Africa (Griffin et al, 2007;Prospero et al, 2005;Smith et al, 2013), potentially contributing to the global transport of genetic information. 15 PBAPs have been identified and characterized using a large range of methods, including traditional methods such as microscopic analysis and cultivation methods, and modern methods using molecular techniques (Caruana, 2011;Després et al, 2012;Griffiths and Decosemo, 1994). However, continuous measurements of PBAPs have been limited, and therefore actual abundances, properties, as well as the origin of PBAPs and their components are still poorly quantified and understood (Burrows et al, 2009a;Burrows et al, 2009b).…”
Section: Introductionmentioning
confidence: 99%